Formulating Strategies Against Student Radicalism: A Case of Madrasah in Indonesia - Shaleh Shaleh; Zamroni Zamroni; Mukminan Mukminan; Zakaria, Abd. Razak bin; Ramadhan, Syahrul (International Journal of Psychosocial Rehabilitation, 2020)
Radical Islamic ideology has penetrated educational institutions in Indonesia. It has the potential to become the seeds of radical movements that threaten the survival of the life of the nation and state. This study aims to explore the madrasah strategies to deal with the threat of extremist radicalism. The authors employed an argumentative exploration that essays a history of the philosophical moderate Islamic attitude, which was supported by relevant recent research findings, government documents, and a review of the theory, and practice of madrasah education in Indonesia. The results of this study indicate that the strategies of madrasah to counter the growth of radicalism is mainstreaming Islamic moderation, which will function as an ideological shield for the younger generation from the threat of extremism, both right-wing, and left-wing. This strategy needs to strengthen the program by developing a blueprint that is supported by stakeholders and regard to the moderate Islamic cultural base that has been built by NU and Muhammadiyah.